Exploration of temperature dependent dielectric relaxation and correlated barrier hopping (CBH) conduction mechanism of hydrothermally synthesized CuO nanoflakes. (18th September 2019) - Jana, Rajkumar; Datta, Joydeep; Sil, Sayantan; Dey, Arka; Pal, Baishakhi; Biswas, Animesh; Ray, Partha Pratim
Abstract: In this study, we have reported the temperature-dependent relaxation and hopping conduction mechanism of the hydrothermally synthesized nanoflake like cupric oxide (CuO) by employing complex impedance spectroscopy technique. The non-Debye type relaxation mechanism has been explored from the impedance and modulus formalism. Frequency dependent ac conductivity analysis suggests that the material follows correlated barrier hopping (CBH) model and also satisfies the Jonscher's universal power law at various temperatures. Moreover, the density of localized states of the synthesized material near Fermi level was estimated at different frequency. We have also elucidated the activation energy, the hopping distance and the maximum barrier height of the materials. It has been observed that the scaling behavior of the conductivity isotherms can be explained by the time temperature superposition (TTS) principle. Two important parameters of the synthesized sample such as the number density of the charge carrier and the charge carrier mobility are also calculated. This study has tried to enlighten the behaviour of relaxation and conduction mechanism of CuO nanoflake at various temperatures and explained it from the theoretical point of view.